PHOTOCATALYTIC DEGRADATION OF MODEL TEXTILE AND ANTIBIOTIC POLLUTANTS USING CARBON NITRIDE-TITANIA NANOCOMPOSITE - Kerim, Takhmina (Nazarbayev University School of Engineering and Digital Sciences, 2025)
This thesis examines the photocatalytic efficiency of carbon nitride-titania (g-C₃N₄-TiO₂) nanocomposites for degrading environmentally persistent pollutants, specifically methylene blue dye and chlortetracycline hydrochloride antibiotic. Photocatalysis, leveraging solar energy, offers a sustainable alternative to traditional wastewater treatment processes, which often inadequately remove emerging contaminants. Recognizing the inherent limitations of g-C₃N₄, particularly rapid electron-hole recombination and narrow visible light absorption, this study aimed to enhance its properties by synthesizing a g-C₃N₄-TiO₂ heterojunction using microwave-assisted methods. The characterization confirmed that TiO₂ integration substantially improved the structural morphology and increased the available reactive surface area of the composite. Photocatalytic degradation experiments demonstrated significantly superior performance of the nanocomposite in pollutant removal compared to pure carbon nitride. The systematic exploration of variables affecting photocatalytic activity, including pH, catalyst loading, and interfering ions, provided valuable insights into optimizing operational conditions. The regeneration studies further underscored the composite's stability and practical applicability for repeated use. Overall, this work highlights the effectiveness and feasibility of the developed g-C₃N₄-TiO₂ photocatalyst in advanced wastewater treatment, contributing positively to sustainable water management practices.
Keywords: Photocatalysis; Carbon Nitride-Titania Nanocomposite; Water Treatment; Methylene Blue; Chlortetracycline Hydrochloride; type of access: embargo